Implementation Of Differentiated Instruction In Multi-Level English Language Classrooms: Strategies And Outcomes - Imran, Fathurrahman; Muhlisin, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to describe the implementation of differentiated instruction in multi-level English language classrooms among undergraduate Management students at Mandalika University of Education. Employing a descriptive quantitative approach, the study involved 35 student participants during the 2025/2026 odd semester. Data were collected through questionnaires, classroom observations, and focus group interviews, then analyzed using descriptive and thematic techniques. Findings reveal that differentiated instruction-adapting materials, teaching processes, student products, and the learning environment-effectively enhances student participation, motivation, and achievement across all proficiency levels. Notably, significant improvement was recorded among students at the basic proficiency level, and the classroom climate became more inclusive and supportive. These results reinforce the role of differentiated instruction as a key strategy for teaching English in heterogeneous higher education settings, though institutional backing and ongoing professional development for instructors remain essential.